Immunolocalization of Aquaporin 1, 2, and 9 in Anuran Testis of the Neotropical Pointedbelly Frog Leptodactylus podicipinus - Bordin, Rafael O. A. [UNESP]; Oliveira, Classius de [UNESP]; Domeniconi, Raquel F. [UNESP] (MDPI, 2024)
Many anuran survival strategies involve hydric regulation, and reproduction is not different. The aquaporin (AQP) family plays an important role in water transport and regulation in many tissues, including the male gonad. The testes undergo various stages of change during the reproductive cycle, and water balance is an important factor for ensuring reproductive success. Considering the relevance of water control in testicular development in anurans and the lack of research regarding the tissue localization of AQP in the male gonad, the present study investigated the expression of three AQPs (1, 2, and 9) in the testis of the neotropical anuran species Leptodactylus podicipinus during two different periods of the reproductive cycle (reproductive and non-reproductive). AQP1 and 2 immunoreactions were found in early germ cells, spermatozoa, Leydig cells, and Sertoli cells, which were more frequently expressed within the reproductive period. AQP1 was also found in the testicular blood vessels. AQP9 was identified predominantly in the epithelium of the intratesticular ducts of reproductive-period individuals. This study presents, for the first time, the localization of AQP1, AQP2, and AQP9 in the testes of an anuran species and the differences in their location during two distinct periods of the reproductive cycle.
Keywords: anura; aquaporin; immunohistochemistry; spermatogenesis